Spatial Expansion, Planning, and Their Influences on the Urban Landscape of Christian Churches in Canton (1582–1732 and 1844–1911) - Li, Yonggu (Religions, 2024)
Canton (present-day Guangzhou, China) has a long history as a trading port and serves as a window for studying the history of Sino-Western cultural exchanges. Canton was a city built under Confucian orders, leading to significant differences (when compared to Christian cities) in urban functional zoning, layout, urban landscape, and methods for shaping spatial order. Therefore, the churches constructed by Christian missionary societies in Canton merit particular attention in missionary history research and urban planning history. Based on local gazetteers, historical maps, export paintings, Western travelogues, and archives at that time, from a cultural landscape perspective, this article compares and analyzes the spatial expansion of Christian churches and their influences on the urban landscape in Canton in two stages. In the late Ming and early Qing dynasties, the spatial layout of the churches indicated an active integration into Canton City. After the Opium War, churches were not only used for religious purposes but also served as symbols asserting the presence of Christians and Western powers (which made the situation more complicated). Missionary societies attracted believers through the construction of public facilities, building Christian communities centered around churches, thereby competing with authorities for spatial power and influencing the urban functional system and spatial layout controlled by the authorities. Comparatively, the Roman Catholic Cathedral has profoundly changed the traditional landscape order in Canton, while the Protestant Dongshan Church interacted more closely with the city.